1973
DOI: 10.1021/j100641a002
|View full text |Cite
|
Sign up to set email alerts
|

Photopolymerization mechanisms. II. Rates of ionic dark addition of benzenesulfinate ions to acrylic monomers

Abstract: The reaction rates for sulfone formation by the ionic dark addition of benzenesulfinate ions to acrylic monomers are compared with the quantum efficiency of monomer free-radical polymerization initiated by dye-triplet redox reaction with benzenesulfinate ions. In aqueous solutions both ionic addition rates and photopolymerization yields are decreased by electron-withdrawing para substituents on benzenesulfinate. A Hammett equation correlation for the rate constants of ionic addition to acrylamide shows a p val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

1978
1978
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 4 publications
0
5
0
1
Order By: Relevance
“…The RC product 3 ab was isolated in a lower yield compared to the use of the corresponding sulfinamide. Although these experiments indicated that our acid‐induced RC procedure can be extended to include the use of sulfinate derivatives,23 they don′t exclude a preliminary sulfinamide hydrolysis step. That was confirmed when the reaction was performed in the presence of 3 Å molecular sieves.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…The RC product 3 ab was isolated in a lower yield compared to the use of the corresponding sulfinamide. Although these experiments indicated that our acid‐induced RC procedure can be extended to include the use of sulfinate derivatives,23 they don′t exclude a preliminary sulfinamide hydrolysis step. That was confirmed when the reaction was performed in the presence of 3 Å molecular sieves.…”
Section: Methodsmentioning
confidence: 96%
“…[21] To evaluate apossible preliminary sulfinamide hydrolysis into sulfinic acidp rior to the nucleophilic attack, [22] the reaction was carried out, under similar reaction conditions, startingf rom an equimolar mixture of sodium p-toluenesulfinate and HBF 4 (Scheme 4b). The RC product 3ab was isolated in al ower yield compared to the use of the corresponding sulfinamide.A lthough these experimentsi ndicated that our acid-induced RC procedure can be extended to include the use of sulfinate derivatives, [23] they don'te xcludeapreliminary sulfinamide hydrolysis step. That was confirmed when the reaction wasp erformed in the presence of 3molecular sieves.…”
mentioning
confidence: 95%
“…When a droplet of resin is exposed to impinging light, physical chemistry mechanisms as cross-link formation are involved. 23,24 This is also valid while polymer curing is due to the enhanced electric field produced by nanoparticles, nanorods, or plasmonic sources. 25−27 The related technique is indicated as photolithography, and more or less complex structures can be realized by coupling light with specific wave fronts and vitrifying only the cured polymer.…”
Section: ■ Introductionmentioning
confidence: 93%
“…Spatially controlled photopolymerization thus represents an interesting tool for the micro- and nanopatterning of polymers and hybrid materials including polymers containing quantum dots with high spatial resolution. , The size of the photopolymerized structures could even reach few nanometers in case of plasmon-induced photopolymerization. In microfabrication by photopolymerization processes, a light beam triggers a polymerization reaction, which results in solidification of the liquid material in the irradiated areas, while nonirradiated areas remain unchanged and can be washed out by suitable organic solvents. When a droplet of resin is exposed to impinging light, physical chemistry mechanisms as cross-link formation are involved. , This is also valid while polymer curing is due to the enhanced electric field produced by nanoparticles, nanorods, or plasmonic sources. The related technique is indicated as photolithography, and more or less complex structures can be realized by coupling light with specific wave fronts and vitrifying only the cured polymer. Based on this process, micro-optical elements (microlenses and waveguides) can be also fabricated at the extremity of optical fibers. , Because of the volume of the irradiation beam that is diffraction limited, the size of the polymer features in the far-field configuration is limited to few hundreds of nanometers.…”
Section: Introductionmentioning
confidence: 99%
“…Arilsulfinatos são co-iniciadores efetivos para polimerização radicalar onde corantes catiônicos atuam como fotoiniciadores em um processo redox [7][8][9][40][41][42][43][44] . Estudos de supressão de fluorescência, medidas de rendimento quântico e estudos de fotólise estabeleceram que o processo de iniciação pode ser representado pelo seguinte esquema cinético (28)…”
Section: Métodos Experimentais Ii) Corante / Sulfinatounclassified